1991
DOI: 10.1161/01.cir.84.5.2054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thromboxane production and complement activation during myocardial ischemia in patients with angina pectoris.

Abstract: Patients with stable angina have chronically increased thromboxane synthesis as assessed by excretion of urinary metabolites. Thromboxane is acutely released into the coronary sinus during pacing-induced ischemia without significant intracoronary platelet aggregation. Complement does not appear to be activated in stable angina during brief and reversible episodes of myocardial ischemia and does not contribute to thromboxane production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…In this study, patients with relatively higher ischaemic thresholds who developed ischaemia only after 2 min of peak-rate pacing were selected for final analysis; the results obviously demonstrated comparable evidence of electrocardiographic and biochemical parameters. The present study appeared to contradict other results [9,25,30, 311 since we obtained decreased plasma thromboxane levels from the CS blood at 2 min of peak-pacing in patients with pacing-induced ischaemia. This presentation was comparable with a decreased (but not negative) myocardial lactate extraction.…”
Section: Transmyocardial Plasma Thromboxane Az Level and Lactate Extrcontrasting
confidence: 99%
“…In this study, patients with relatively higher ischaemic thresholds who developed ischaemia only after 2 min of peak-rate pacing were selected for final analysis; the results obviously demonstrated comparable evidence of electrocardiographic and biochemical parameters. The present study appeared to contradict other results [9,25,30, 311 since we obtained decreased plasma thromboxane levels from the CS blood at 2 min of peak-pacing in patients with pacing-induced ischaemia. This presentation was comparable with a decreased (but not negative) myocardial lactate extraction.…”
Section: Transmyocardial Plasma Thromboxane Az Level and Lactate Extrcontrasting
confidence: 99%
“…56,58,75,76,78 Daily aspirin doses as low as 30 mg to 50 mg inactivate the platelet cyclo-oxygenase-1 enzyme and inhibit thromboxane production . [79][80][81] Studies comparing lower (75 mg to 150 mg) with higher aspirin doses have consistently found comparable ischemic event rates with either dose when used as monotherapy or when combined with the P2Y 12 inhibitor clopidogrel . [56][57][58][59][60]78 The efficacy of ticagrelor seems to be decreased in patients treated with higher aspirin doses (≥300 mg daily) versus lower aspirin doses (≤100 mg daily) .…”
Section: Aspirin Dosing In Patients Treated With Dapt: Recommendationmentioning
confidence: 99%
“…In summary, these results provide further support for the importance of TxA 2 in eliciting arrhythmias and may have special significance in cases where the level of TxA 2 is elevated above normal. One obvious example is the increase in TxA 2 during myocardial ischemia (18,29). However, another example involves the recent reports that Vioxx, an inhibitor of the inducible form of COX-2, may increase the risk of cardiovascular problems.…”
Section: Discussionmentioning
confidence: 99%